Pest Identification Guide: Solanum (Pepper) Whitefly, Aleurotrachelus trachoides - Nicole A Casuso; Hugh A. Smith (EDIS, 2018)
Considered an emerging pest in Florida, the solanum whitefly has been in the state since at least the 1960s. It eats pepper, eggplant, and tomato, as well as other food crops, ornamental plants, and weeds. Learn to identify the little pest with this handy, 2-page guide written by Nicole A. Casuso and Hugh A. Smith and published by the UF/IFAS Entomology and Nematology Department. https://edis.ifas.ufl.edu/in1201